0 like 0 dislike
Which equivalent equation results when completing the square to solve x2 − 8x + 7 = 0
by

1 Answer

0 like 0 dislike
(x - 4)² = 9

Step-by-step explanation:

x² - 8x + 7 = 0 ( add 7 to both sides )

x² - 8x = - 7

to complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(- 4)x + 16 = - 7 + 16

(x - 4)² = 9 ← equation to be solved

take the square root of both sides

x - 4 = ± [tex]\sqrt{9}[/tex] = ± 3 ( add 4 to both sides )

x = 4 ± 3

then solutions are

x = 4 - 3 = 1 or x = 4 + 3 = 7
by
Welcome to AskTheTask.com, where understudies, educators and math devotees can ask and respond to any number related inquiry. Find support and replies to any numerical statement including variable based math, geometry, calculation, analytics, geometry, divisions, settling articulation, improving on articulations from there, the sky is the limit. Find solutions to numerical problems. Help is consistently 100 percent free!

Questions

No related questions found